Imprinting ink for glass surface and preparation method thereof

By using an imprinted ink formulation containing deionized water, carboxymethylcellulose, pigment and silane coupling agent KH560 on the glass surface, and adding filler improvers, the problem of insufficient ink adhesion and stability in the prior art is solved, and more efficient glass texture production is achieved.

CN119592128APending Publication Date: 2025-03-11GUANGDONG YOULIAN MAILUI NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411786463.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In the existing glass texture production process, the adhesion performance of the imprinted ink is poor, and the performance stability is poor under acid corrosion, water washing and solvent conditions, which limits the efficiency of the product.

Method used

The imprinted ink formula includes deionized water, carboxymethyl cellulose, pigment and silane coupling agent KH560, and by adding filler improvers, it is used to blend materials such as titanium dioxide, sodium lignin sulfonate solution and sodium alginate combined with talc powder to improve the adhesion and stability of the ink.

Benefits of technology

It significantly improves the adhesion performance of the imprinted ink on the glass surface, and maintains good performance stability under acid corrosion, water washing and solvent conditions, improving the efficiency of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses imprint ink for a glass surface. The imprint ink comprises the following raw materials in parts by weight; the paint comprises the following components in parts by weight: 10-15 parts of deionized water, 2-5 parts of carboxymethyl cellulose, 2-5 parts of pigment, 2-5 parts of silane coupling agent KH560 and 4-7 parts of filler modifier. By filling and improving the filler improver, the performance of the product is further improved, the adhesive force performance effect of the imprinting ink is remarkable, and the performance stability effect of the product under the conditions of acid corrosion, water washing and solvent is remarkable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of embossing inks, and in particular to an embossing ink for glass surfaces and a preparation method thereof. Background Art

[0002] At present, the production process of glass texture mainly includes the process of reproducing the texture pattern by screen printing and UV ink. The existing embossing ink has poor adhesion performance, and the product has poor performance stability under acid corrosion, water washing and solvent conditions, which limits the use efficiency of the product. Based on this, the present invention further improves the process. Summary of the invention

[0003] In view of the defects of the prior art, the purpose of the present invention is to provide an embossing ink for glass surface and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0004] The present invention solves the technical problem by adopting the following technical solution: The present invention provides an embossing ink for glass surface, comprising the following raw materials in parts by weight: 10-15 parts of deionized water, 2-5 parts of carboxymethyl cellulose, 2-5 parts of pigment, 2-5 parts of silane coupling agent KH560 and 4-7 parts of filler improver.

[0005] Preferably, the pigment is copper chrome black.

[0006] Preferably, the preparation method of the filler improver is: S11: preheating titanium dioxide at 50-55° C. for 10-15 minutes to obtain preheated titanium dioxide, and preparing a sodium lignin sulfonate solution having a mass fraction of 5-7%; S12: then adding 5-7 parts of preheated titanium dioxide and 1-3 parts of carboxymethyl cellulose to 4-7 parts of sodium lignin sulfonate solution, and then adding 2-4 parts of sodium citrate to fully blend to obtain a titanium dioxide agent; S13: titanium dioxide, sodium alginate and talc are mixed in a weight ratio of 5:3 and subjected to ball milling improvement treatment. After the ball milling is completed, the mixture is washed with water and dried to obtain a filler improver.

[0007] Preferably, the mass fraction of the sodium lignin sulfonate solution is 2-5%.

[0008] Preferably, the ball milling speed of the ball milling improvement treatment is 1000-1500r / min, and the ball milling is 2h.

[0009] Preferably, the preparation method of the sodium alginate combined with talc is: The sodium alginate powder is first mixed with the sodium dodecylbenzene sulfonate solution to obtain a sodium alginate solution; 2-5 parts of sodium alginate solution are added to 4-7 parts of lanthanum chloride solution, and then 2-4 parts of talc and 1-3 parts of stearic acid are added and mixed to obtain a sodium alginate combined with talc.

[0010] Preferably, the mass fraction of the sodium dodecylbenzene sulfonate solution is 2-5%.

[0011] Preferably, the mass fraction of the lanthanum chloride solution is 5-7%.

[0012] Preferably, the mass fraction of the lanthanum chloride solution is 6%.

[0013] A method for preparing an embossing ink for a glass surface comprises the following steps: The raw materials are weighed according to weight, and then the raw materials are ball-milled to mix evenly. After the ball-milling is completed, the imprinting ink is obtained.

[0014] Preferably, the ball milling speed of the ball milling mixing treatment is 1000-1500 r / min, and the ball milling is performed for 2 hours.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The embossing ink on the glass surface of the present invention is prepared by deionized water, carboxymethyl cellulose, pigment and silane coupling agent KH560, and a filler improver is added to blend and coordinate with each other. The titanium dioxide in the filler improver is preheated, blended with a sodium lignin sulfonate solution, and then blended and coordinated with the carboxymethyl cellulose. At the same time, sodium alginate and talcum powder are combined. The sodium alginate powder is first blended evenly with a sodium dodecylbenzene sulfonate solution to improve the coordination of the sodium alginate. The lanthanum chloride solution, talcum powder and stearic acid are blended and coordinated. The performance of the product is further improved by filling and improving the filler improver, and the adhesion performance of the embossing ink is remarkable. The performance stability of the product under the conditions of acid decay, water washing and solvent is remarkable. DETAILED DESCRIPTION

[0016] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] The embossing ink for glass surface of this embodiment includes the following raw materials in parts by weight: 10-15 parts of deionized water, 2-5 parts of carboxymethyl cellulose, 2-5 parts of pigment, 2-5 parts of silane coupling agent KH560 and 4-7 parts of filler improver.

[0018] The pigment of this embodiment is copper chrome black.

[0019] The preparation method of the filler improver of the present embodiment is: S11: preheating titanium dioxide at 50-55° C. for 10-15 minutes to obtain preheated titanium dioxide, and preparing a sodium lignin sulfonate solution having a mass fraction of 5-7%; S12: then adding 5-7 parts of preheated titanium dioxide and 1-3 parts of carboxymethyl cellulose to 4-7 parts of sodium lignin sulfonate solution, and then adding 2-4 parts of sodium citrate to fully blend to obtain a titanium dioxide agent; S13: titanium dioxide, sodium alginate and talc are mixed in a weight ratio of 5:3 and subjected to ball milling improvement treatment. After the ball milling is completed, the mixture is washed with water and dried to obtain a filler improver.

[0020] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 2-5%.

[0021] The ball milling speed of the improved ball milling process in this embodiment is 1000-1500 r / min, and the ball milling is performed for 2 hours.

[0022] The preparation method of sodium alginate combined with talcum powder in this embodiment is: The sodium alginate powder is first mixed with the sodium dodecylbenzene sulfonate solution to obtain a sodium alginate solution; 2-5 parts of sodium alginate solution are added to 4-7 parts of lanthanum chloride solution, and then 2-4 parts of talc and 1-3 parts of stearic acid are added and mixed to obtain a sodium alginate combined with talc.

[0023] The mass fraction of the sodium dodecylbenzenesulfonate solution of the present embodiment is 2-5%.

[0024] The mass fraction of the lanthanum chloride solution of the present embodiment is 5-7%.

[0025] The mass fraction of the lanthanum chloride solution of the present embodiment is 6%.

[0026] A method for preparing an embossing ink for a glass surface in this embodiment includes the following steps: The raw materials are weighed according to weight, and then the raw materials are ball-milled to mix evenly. After the ball-milling is completed, the imprinting ink is obtained.

[0027] The ball milling speed of the ball milling mixing treatment in this embodiment is 1000-1500r / min, and the ball milling is 2h.

[0028] Example 1. The embossing ink for glass surface of this embodiment includes the following raw materials in parts by weight: 10 parts of deionized water, 2 parts of carboxymethyl cellulose, 2 parts of pigment, 2 parts of silane coupling agent KH560 and 4 parts of filler improver.

[0029] The pigment of this embodiment is copper chrome black.

[0030] The preparation method of the filler improver of the present embodiment is: S11: preheating titanium dioxide at 50° C. for 10 min to obtain preheated titanium dioxide, and preparing a sodium lignin sulfonate solution with a mass fraction of 5%; S12: then adding 5 parts of preheated titanium dioxide and 1 part of carboxymethyl cellulose to 4 parts of sodium lignin sulfonate solution, and then adding 2 parts of sodium citrate to fully blend to obtain a titanium dioxide agent; S13: titanium dioxide, sodium alginate and talc are mixed in a weight ratio of 5:3 and subjected to ball milling improvement treatment. After the ball milling is completed, the mixture is washed with water and dried to obtain a filler improver.

[0031] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 2%.

[0032] The ball milling speed of the ball milling improvement treatment in this embodiment is 1000r / min, and the ball milling is 2h.

[0033] The preparation method of sodium alginate combined with talcum powder in this embodiment is: The sodium alginate powder is first mixed with the sodium dodecylbenzene sulfonate solution to obtain a sodium alginate solution; 2 parts of sodium alginate solution are added to 4 parts of lanthanum chloride solution, and then 2 parts of talc and 1 part of stearic acid are added and mixed thoroughly to obtain a sodium alginate combined with talc.

[0034] The mass fraction of the sodium dodecylbenzenesulfonate solution of the present embodiment is 2%.

[0035] The mass fraction of the lanthanum chloride solution of the present embodiment is 5%.

[0036] A method for preparing an embossing ink for a glass surface in this embodiment includes the following steps: The raw materials are weighed according to weight, and then the raw materials are ball-milled to mix evenly. After the ball-milling is completed, the imprinting ink is obtained.

[0037] The ball milling speed of the ball milling mixing treatment in this embodiment is 1000r / min, and the ball milling is 2h.

[0038] Example 2. The embossing ink for glass surface of this embodiment includes the following raw materials in parts by weight: 12 parts of deionized water, 3 parts of carboxymethyl cellulose, 3 parts of pigment, 3 parts of silane coupling agent KH560 and 5 parts of filler improver.

[0039] The pigment of this embodiment is copper chrome black.

[0040] The preparation method of the filler improver of the present embodiment is: S11: preheating titanium dioxide at 55° C. for 15 min to obtain preheated titanium dioxide, and preparing a sodium lignin sulfonate solution with a mass fraction of 7%; S12: then adding 7 parts of preheated titanium dioxide and 3 parts of carboxymethyl cellulose to 7 parts of sodium lignin sulfonate solution, and then adding 4 parts of sodium citrate to fully blend to obtain a titanium dioxide agent; S13: titanium dioxide, sodium alginate and talc are mixed in a weight ratio of 5:3 and subjected to ball milling improvement treatment. After the ball milling is completed, the mixture is washed with water and dried to obtain a filler improver.

[0041] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 2-5%.

[0042] The ball milling speed of the improved ball milling process in this embodiment is 1000-1500 r / min, and the ball milling is performed for 2 hours.

[0043] The preparation method of sodium alginate combined with talcum powder in this embodiment is: The sodium alginate powder is first mixed with the sodium dodecylbenzene sulfonate solution to obtain a sodium alginate solution; 5 parts of sodium alginate solution were added to 7 parts of lanthanum chloride solution, and then 4 parts of talc and 3 parts of stearic acid were added and mixed to obtain a sodium alginate combined with talc.

[0044] The mass fraction of the sodium dodecylbenzenesulfonate solution of the present embodiment is 5%.

[0045] The mass fraction of the lanthanum chloride solution of the present embodiment is 7%.

[0046] A method for preparing an embossing ink for a glass surface in this embodiment includes the following steps: The raw materials are weighed according to weight, and then the raw materials are ball-milled to mix evenly. After the ball-milling is completed, the imprinting ink is obtained.

[0047] The ball milling speed of the ball milling mixing treatment in this embodiment is 1500r / min, and the ball milling is 2h.

[0048] Example 3. The embossing ink for glass surface of this embodiment includes the following raw materials in parts by weight: 12.5 parts of deionized water, 3.5 parts of carboxymethyl cellulose, 3.5 parts of pigment, 3.5 parts of silane coupling agent KH560 and 5.5 parts of filler improver.

[0049] The pigment of this embodiment is copper chrome black.

[0050] The preparation method of the filler improver of the present embodiment is: S11: preheating titanium dioxide at 52.5°C for 12.5 minutes to obtain preheated titanium dioxide, and preparing a sodium lignin sulfonate solution with a mass fraction of 6%; S12: then add 6 parts of preheated titanium dioxide and 2 parts of carboxymethyl cellulose to 5.5 parts of sodium lignin sulfonate solution, and then add 3 parts of sodium citrate to fully blend to obtain titanium dioxide agent; S13: titanium dioxide, sodium alginate and talc are mixed in a weight ratio of 5:3 and subjected to ball milling improvement treatment. After the ball milling is completed, the mixture is washed with water and dried to obtain a filler improver.

[0051] The mass fraction of the sodium lignin sulfonate solution in this embodiment is 3.5%.

[0052] The ball milling speed of the ball milling improvement treatment in this embodiment is 1250r / min, and the ball milling is 2h.

[0053] The preparation method of sodium alginate combined with talcum powder in this embodiment is: The sodium alginate powder is first mixed with the sodium dodecylbenzene sulfonate solution to obtain a sodium alginate solution; 3.5 parts of sodium alginate solution were added to 5.5 parts of lanthanum chloride solution, and then 3 parts of talc and 2 parts of stearic acid were added and mixed to obtain a sodium alginate combined with talc.

[0054] The mass fraction of the sodium dodecylbenzenesulfonate solution of the present embodiment is 3.5%.

[0055] The mass fraction of the lanthanum chloride solution of the present embodiment is 6%.

[0056] A method for preparing an embossing ink for a glass surface in this embodiment includes the following steps: The raw materials are weighed according to weight, and then the raw materials are ball-milled to mix evenly. After the ball-milling is completed, the imprinting ink is obtained.

[0057] The ball milling speed of the ball milling mixing treatment in this embodiment is 1250r / min, and the ball milling is 2h.

[0058] Comparative Example 1. The difference from Example 3 is that no filler improver is added.

[0059] Comparative Example 2. The difference from Example 3 is that no sodium alginate combined with talc is added to the filler improver.

[0060] Comparative Example 3. The difference from Example 3 is that no titanium dioxide is added to the filler improver.

[0061] Comparative Example 4. The difference from Example 3 is that no preheated titanium dioxide is added to the titanium dioxide agent.

[0062] Comparative Example 5. The difference from Example 3 is that no talc is added to the sodium alginate combined with talc.

[0063] Comparative Example 6. The difference from Example 3 is that no sodium alginate liquid is added to the sodium alginate combined with talc.

[0064] The product performance tests of Examples 1-3 and Comparative Examples 1-6 are as follows:

[0065] It can be seen from Comparative Examples 1-6 and Example 3 that the product of Example 3 has excellent adhesion, and the product has significant acid resistance, water resistance and solvent resistance stability effects; No filler improver is added to the product, and the performance of the product deteriorates significantly. At the same time, no sodium alginate combined with talc agent is added to the filler improver, and no titanium dioxide agent is added to the filler improver. The performance of the product deteriorates significantly. In addition, no preheated titanium dioxide is added to the titanium dioxide agent, no talc is added to the sodium alginate combined with talc agent, and no sodium alginate liquid is added to the sodium alginate combined with talc agent. All of them are not as good as the best effect produced by the method adopted by the present invention. The filler improver of the present invention has a significant improvement effect.

[0066] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0067] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A printing ink for glass surface, characterized in that: It comprises the following raw materials in parts by weight; 10-15 parts of deionized water, 2-5 parts of carboxymethyl cellulose, 2-5 parts of pigment, 2-5 parts of silane coupling agent KH560 and 4-7 parts of filler improver.

2. The embossing ink for glass surface according to claim 1, characterized in that: The pigment is copper chrome black.

3. The embossing ink for glass surface according to claim 1, characterized in that: The preparation method of the filler improver is: S11: preheating titanium dioxide at 50-55° C. for 10-15 minutes to obtain preheated titanium dioxide, and preparing a sodium lignin sulfonate solution having a mass fraction of 5-7%; S12: then adding 5-7 parts of preheated titanium dioxide and 1-3 parts of carboxymethyl cellulose to 4-7 parts of sodium lignin sulfonate solution, and then adding 2-4 parts of sodium citrate to fully blend to obtain a titanium dioxide agent; S13: titanium dioxide, sodium alginate and talc are mixed in a weight ratio of 5:3 and subjected to ball milling improvement treatment. After the ball milling is completed, the mixture is washed with water and dried to obtain a filler improver.

4. The embossing ink for glass surface according to claim 3, characterized in that: The mass fraction of the sodium lignin sulfonate solution is 2-5%; the ball milling speed of the ball milling improvement treatment is 1000-1500r / min, and the ball milling is performed for 2h.

5. The embossing ink for glass surface according to claim 3, characterized in that: The preparation method of the sodium alginate combined with talc is as follows: The sodium alginate powder is first mixed with the sodium dodecylbenzene sulfonate solution to obtain a sodium alginate solution; 2-5 parts of sodium alginate solution are added to 4-7 parts of lanthanum chloride solution, and then 2-4 parts of talc and 1-3 parts of stearic acid are added and mixed to obtain a sodium alginate combined with talc.

6. The embossing ink for glass surface according to claim 5, characterized in that: The mass fraction of the sodium dodecylbenzene sulfonate solution is 2-5%.

7. The embossing ink for glass surface according to claim 6, characterized in that: The mass fraction of the lanthanum chloride solution is 5-7%.

8. The embossing ink for glass surface according to claim 7, characterized in that: The mass fraction of the lanthanum chloride solution is 6%.

9. A method for preparing an embossing ink for a glass surface according to any one of claims 1 to 8, characterized in that: The following steps are involved: The raw materials are weighed according to weight, and then the raw materials are ball-milled to mix evenly. After the ball-milling is completed, the imprinting ink is obtained.

10. The method for preparing an embossing ink for a glass surface according to claim 9, characterized in that: The ball milling speed of the ball milling mixing treatment is 1000-1500r / min, and the ball milling is performed for 2h.